Impact of Socio Demographic Factors on Individuals’ Risk Attitude: A Study of Jaffna Municipal Council Area - Mathanika, T.; Tharshiga, P.; Yogendrarajah, R. (National Centre for Advanced Studies (NCAS), 2022)
Risk behaviour of individuals is influenced by many factors. A socio demographic factor plays an important role in explaining the risk behaviour of individuals. The main aim of this study is to examine the impact of socio demographic factors on risk attitude of individuals. For this purpose, following a case study approach, 150 individuals were selected as the sample in Jaffna Municipal Council area based on cluster sampling method. Primary data was collected by using a questionnaire and interviews. Gender, Age, Educational Level, Monthly income, Marital status, Religion, Investment experience, Investment knowledge were used as the measures of socio demographic factors whereas Risk seeker and Risk averter were used as the measures of risk attitude. Three hypotheses were tested using correlation, regression and one way ANOVA analysis. This study found that socio demographic factors of age, marital status, monthly income, and investment experience and investment knowledge have significant relationship with risk attitude while socio demographic factors of gender, education level and religion have no relationship with risk attitude of individuals. Further, this study revealed that the socio demographic factors have significant impact on risk attitude except gender, educational level and religion. The results also showed that there is a significant difference in risk attitude amongst individuals from different income groups. Although this study supports a number of earlier studies, it could not provide conclusive evidence on some important issues. Furthermore, the finding of the study can be considered as helpful for some persons or institutions.
Keywords: Socio demographic factors; Risk attitude; Risk averter; Risk seeker; Jaffna Municipal Council area